Maternal and neonatal outcomes in women with history of coronary artery disease. Issue 5 (18th September 2019) - Cauldwell, Matthew; Steer, Philip J; von Klemperer, Katherine; Kaler, Mandeep; Grixti, Sarah; Hale, Joanna; O'Heney, Josie; Warriner, David; Curtis, Stephanie; Mohan, Aarthi R; Dockree, Samuel; Mackillop, Lucy; et al.
Abstract : Background: Pregnancy outcomes in women with pre-existing coronary artery disease (CAD) are poorly described. There is a paucity of data therefore on which to base clinical management to counsel women, with regard to both maternal and neonatal outcomes. Method: We conducted a retrospective multicentre study of women with established CAD delivering at 16 UK specialised cardiac obstetric clinics. We included pregnancies of 24 weeks' gestation or more, delivered between January 1998 and October 2018. Data were collected on maternal cardiovascular, obstetric and neonatal events. Results: 79 women who had 92 pregnancies (94 babies including two sets of twins) were identified. 35.9% had body mass index >30% and 24.3% were current smokers. 18/79 (22.8%) had prior diabetes, 27/79 (34.2%) had dyslipidaemia and 21/79 (26.2%) had hypertension. The underlying CAD was due to atherosclerosis in 52/79 (65.8%), spontaneous coronary artery dissection (SCAD) in 11/79 (13.9%), coronary artery spasm in 7/79 (8.9%) and thrombus in 9/79 (11.4%). There were six adverse cardiac events (6.6% event rate), one non-ST elevation myocardial infarction at 23 weeks' gestation, two SCAD recurrences (one at 26 weeks' gestation and one at 9 weeks' postpartum), one symptomatic deterioration in left ventricular function and two women with worsening angina. 14% of women developed pre-eclampsia, 25% delivered preterm and 25% of infants were born small for gestational age. Conclusion: Women with established CAD have relatively low rates of adverse cardiac events in pregnancy. Rates of adverse obstetric and neonatal events are greater, highlighting the importance of multidisciplinary care.